An exploratory study of the relationship between in-training examination percentiles of anesthesiology residents and the vermunt inventory of learning styles - Lloyd, Sara H (Kansas State University, 2007)
This study explored the relationship between anesthesiology residents' In Training Examination (ITE) percentile ranks and learning styles and domains with the variables of gender, ethnicity, and postgraduate year (PGY). The ITE is a national examination given annually as a measure of cognitive achievement. The learning style instrument was the adapted Vermunt Inventory of Learning Styles (ILS), a diagnostic learning style instrument designed for use with university-level students. The study included 112 anesthesiology residents in anesthesiology graduate medical education (GME) at four universities (five sites) during the 2006-2007 PGY. Responses to the surveys were analyzed using descriptive statistics, the Pearson product-moment correlations, and stepwise and backward elimination regression analysis. The results indicated that the residents' ITE percentile ranks had a bimodal curve. The ILS has 20 scales representing four learning domains factored into four learning styles. The relationships of the learning styles with the ITE percentile ranks were significant for two learning styles: positive for the meaning directed learning style (MDLS) and negative for the undirected learning style (UDLS). Analysis of the scales comprising the MDLS (seven) and UDLS (five) revealed significant relationships for 6 of the 12 scales for the anesthesiology residents (five positive, one negative). An analysis of the domain scale relationships for the other eight scales identified an additional two scales positively related to ITE percentile ranks: vocation oriented and analyzing. The significant scales positively identified with ITE percentile ranks included relating and structuring, concrete processing, two self-regulation scales, construction of knowledge, analyzing and vocation oriented. The only scale significant with ITE percentile ranks was ambivalent, which was negative. The potential exists that the UDLS can identify, in part, residents at risk academically. The positive relationship of the meaning directed learning style and the two significant, positive scales (analyzing and vocation oriented) with ITE percentile ranks offered an indication of learning styles and strategies of residents with higher cognitive achievement outcomes. These learning strategies have the potential to help residents learn how to learn more effectively.
Keywords: Education, Adult and Continuing (0516); Education, Higher (0745); Education, Social Sciences (0534); Education, Tests and Measurements (0288); Education, Adult and Continuing (0516); Education, Educational Psychology (0525); Education, Higher (0745)